ANALISIS KEBUTUHAN DAN KETERSEDIAAN AIR BERSIH DI KELURAHAN PASIR PUTIH KABUPATEN MANOKWARI (Studi Kasus : RT 002/RW 002 Kelurahan Pasir Putih Kabupaten Manokwari): ANALISIS KEBUTUHAN DAN KETERSEDIAAN AIR BERSIH DI KELURAHAN PASIR PUTIH KABUPATEN MANOKWARI (Studi Kasus : RT 002/RW 002 Kelurahan Pasir Putih Kabupaten Manokwari) - Felisia Malatta Banioni; Olivia Marie Caesaria Kesauliya; Adonia Pasinggi (JISTECH: Journal of Information Science and Technology, 2025)
The annual increase in population leads to a continuous rise in the demand for clean water. This situation raises concerns about future needs and the availability of clean water. To understand the comparison between clean water requirements and the available water supply, a directed and systematic study is required. For this purpose, an analysis is needed to compare the available water supply with the population's water needs, thereby determining the level of sufficiency and any potential shortages that may arise. This research aims to analyze the magnitude of clean water needs and the level of clean water availability in RT 002/RW 002, Pasir Putih Ward, Manokwari Regency. The study employs a quantitative approach, with a sample of 28 respondents from the location. Data analysis is conducted through stages including population projection, clean water needs analysis, and clean water availability analysis, to assess the balance between water needs and availability over the research period from 2025 to 2035. Research results show that the need for clean water is increasing every year in line with the growth of the population. In 2035, the need for clean water is projected at 1,494 liters per second, while the total availability of clean water in the research area is recorded to be far below the existing water needs. The per capita water availability in the RT 002/RW 002 area shows a decline from year to year. In 2025, the per capita water availability value is 0.022 liters per person per second, and it decreases to 0.019 liters per person per second in 2035. This decline is caused by the continuous increase in the population, while the flow rate of the water source remains constant at 4,715 liters per second.